Calculation of energy losses in relation to its quality in fuzzy form in rural distribution networks - Тимчук, Сергій Олександрович; Мирошник, Александр Александрович (Eastern-European Journal of Enterprise Technologies, 2015)
The level of electricity loss indicates the efficiency level of electricity supply system. Precise calculation of electricity loss, especially in rural networks (0.38/0.22 kW), is not always possible. It is even more difficult to structure losses at changing PQI since there emerges a problem of reliability of the background information. We suggest solving the difficult problem by means of presenting electricity losses in fuzzy form, which allows to observe dynamic changes of losses at changing PQI as well as to compare the level of losses in the network with the norm. The emerging problem of uncertainty of the background information is solved with the help of fuzzy sets. Meanwhile, the rate of correspondence of PQI fuzzy values to vague standards of power quality should be estimated at their intersection. The intersection of fuzzy numbers can be evaluated due to the area of the figure created by the intersection membership function. Instead of considering the existing determined dependencies of electricity losses, we suggest presenting losses in fuzzy form with regard to peculiarities of particular loads and elements of power network. We have suggested expressions for the calculation of electricity losses for different loads, considered losses from asymmetry and nonsinusoidality for asynchronous engines and power transformers as well as presented graphs that distinctly show the range and dynamic changes of electricity losses depending on PQI. The importance of the obtained findings consists in the new possibility of raising the informational content of the evaluated electricity losses when the background information is uncertain.